SPECTRAL THEORY OF HILFER FRACTIONAL BESSEL OPERATOR - Panakhov, Etibar; Bas, Erdal; Ercan, Ahu (Baku State Univ, Inst Applied Mathematics, 2018)
[Abstract Not Available]
6th International Conference on Control and Optimization with Industrial Applications (COIA) -- JUL 11-13, 2018 -- Baku, AZERBAIJAN
Keywords: Fractional; Bessel operator; eigenvalues; Hilfer